1979
DOI: 10.1016/0002-9416(79)90206-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of temporomandibular joint adaptations to protrusive function

Abstract: M uch has been published in the clinical and basic science literature on the growth of the temporomandibular joint. An area of significant controversy is the question of whether the growth of the temporomandibular joint, and of the mandibular condyle in particular, can be influenced to any significant degree through therapeutic or experimental intervention. Despite the number of clinical and experimental studies of this question, no universal agreement has been reached regarding the potential for adaptation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(106 citation statements)
references
References 16 publications
4
89
1
12
Order By: Relevance
“…4,5 A wide range of functional appliances aimed to stimulate mandibular growth by forward posturing of the mandible is available to correct this type of skeletal and occlusal disharmony. 5 Although many studies in animals have demonstrated that skeletal mandibular changes can be produced by posturing the mandible forward, [6][7][8] the effects on humans are more equivocal and controversial. Many treatment protocols, sample sizes, and research approaches have led to disparate outcomes in studies on human subjects.…”
mentioning
confidence: 99%
“…4,5 A wide range of functional appliances aimed to stimulate mandibular growth by forward posturing of the mandible is available to correct this type of skeletal and occlusal disharmony. 5 Although many studies in animals have demonstrated that skeletal mandibular changes can be produced by posturing the mandible forward, [6][7][8] the effects on humans are more equivocal and controversial. Many treatment protocols, sample sizes, and research approaches have led to disparate outcomes in studies on human subjects.…”
mentioning
confidence: 99%
“…Various experimental models that have evaluated mandibular growth in response to advancement have been published (Carlson, 1999;Mcnamara & Bryan, 1987;Mcnamara & Carlson, 1979;Meikle, 2007). Analyses were made by means of radiographic (Liu et al, 2007a), histological (Liu et al, 2007b), and immunohistochemicalstudies (Sato et al, 2006), comparison of different consistencies of food (Bresin & Kiliaridis, 2002;Maki, Nishioka, Shioiri, Takahashi, & Kimura, 2002), calcium restriction (Watanabe, Imamura, Uchikanbori, Fujita, & Maki, 2008), Type X collagen expression (Rabie & Hägg, 2002;Rabie, Xiong, & Hägg, 2004;Shen, Zhao, Kaluarachchi, & Rabie, 2006), Type II collagen expression Tuominen et al, 1996), transcription factor Sox 9 (Papadopoulou et al, 2007;Rabie, She & Hägg, 2003a) and vascular endothelial growth factor -VEGF (Rabie & Hägg, 2002;Rabie, Shum, & Chayanupatkul, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies by McNamara et al [27][28][29] in Macaque monkeys incorporating tantalum implants have identified similar changes and highlighted the relevance of treatment timing of the treatment, based on reported changes in the electromyographic (EMG) activity in the lateral pterygoid muscles. Observation was made of the length of time required to produce additional bone rather than cartilage, with the latter being a less permanent structure.…”
Section: Experiments On Primatesmentioning
confidence: 92%